Critical Velocity and Pressure Drop for Horizontal Pneumatic Conveying in Non-circular Pipes - Wirth, Karl-Ernst; Molerus, Otto (German Chemical Engineering, 1986)
Starting from the calculation of additional pressure drop for horizontal pneumatic strand-type conveying in circular pipes, the additional pressure drop and critical velocity for different pipe cross-sections were calculated. The relationships derived for horizontal pneumatic conveying in non-circular pipes were compared with measurements in non-circular pipes during hydraulic conveying. The comparison shows that there is a qualitative agreement between theory and measurement. It follows from the calculations and measurements that, in general, pipes with low cross-sectional profiles can be operated at lower fluid velocities than circular pipes with identical cross-sectional areas.
UnivIS-Import:2015-03-05:Pub.1986.tech.ITC.mechve.critic_40